Highly efficient removal of glyphosate from water by hierarchical-pore UiO-66: Selectivity and effects of natural water particles. (15th August 2022) - Tao, Yue; Fang, Fei; Lv, Quankun; Qin, Wenkai; He, Xiudan; Zhang, Yan; Zhou, Yi; Li, Xuede; Li, Jie
Abstract: The selective removal of glyphosate (GP) from aqueous environments is crucial for ensuring human health and environmental sustainability. The preparation of hierarchical-pore MOFs and the reasonable regulation of the pore size are effective strategies for achieving selective removal. In this study, we applied hierarchical-pore UiO-66 analogues (HUiO-66s) synthesized by the template technique through a mild method for the removal of GP from water. The results showed that the maximum adsorption capacity of HUiO-66s was as high as 400 mg/g, which is higher than that of most reported adsorbents. Notably, HUiO-66s showed the highest adsorption rate and distribution coefficient for GP in a multivariate system containing different organophosphorus pesticides and antibiotics, exhibiting suitable selective adsorption performance for GP. Furthermore, GP adsorption onto HUiO-66-2 (prepared from 2 mL of MOF-5 template) did not affect the presence of competing anions and humic acids. Naturally occurring particles in the water body had an enhanced (i.e., Al2 O3, sepiolite, and montmorillonite), reduced (i.e., illite and SiO2 ), or insignificant (i.e., kaolin) effect on the GP adsorption rate of HUiO-66-2. Further analysis based on the bulk adsorption results and microscopic characterisation indicated that the pore structure synergistically occurred with metal-ligand bonding, hydrogen bonding, and electrostatic interactions, which together determined the GP adsorption. Overall, the high adsorption and apparent adsorption selectivity of HUiO-66s facilitated the rapid separation and removal of GP in complex aqueous environments. Our findings provide insights into the transport and fate of MOFs and contaminants in natural aquatic systems. Highlights: HUiO-66s showed a maximum adsorption capacity of 400 mg/g for glyphosate (GP). HUiO-66-2 exhibited significant selective adsorption behaviour for GP in the multi-pollutant mixed system. The effect of the presence of natural aquatic particles on the adsorption GP of HUiO-66-2 was investigated. The adsorption mechanism of HUiO-66-2 on GP was traced by FTIR and XPS.